Budaya Sekolah - Muhammad Afifullah Nizary; Tasman Hamami (At-Tafkir, 2020)
The school is analogous to the environment in such a way that its citizens can obtain education and learning services that are worthy of expectations. School culture is a characteristic, character, and image owned by the school in the wider community. The proper and precise application of school culture will have a significant influence on student learning activities, it can also affect teachers to do more efficient and effective work to achieve good teacher performance. Quality school culture will appear if there are a concern and active participation of all the school citizens. The research uses a library research method in which the source is used in the form of books, articles, and other sources related to the research title. The purpose of this research is to describe and know how to implement school culture development. This research discusses the understanding of culture, the role of school culture, and the development of school culture. Developing school culture certainly needs a sense of togetherness and responsibility to the school of all the school citizens under the command of the principal and coaching from the supervisor. Development of quality school culture is determined by the quality of education. Good and quality education is the basis for the development and progress of the school to move towards higher and quality levels